1992
DOI: 10.1002/1097-0142(19921115)70:10<2468::aid-cncr2820701013>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical ductal carcinoma in situ of the breast: Treatment by local excision and surveillance alone

Abstract: Background. Mammography has led to earlier detection of subclinical ductal carcinoma in situ (DCIS) of the breast either as nonpalpable calcifications or as an incidental finding in a biopsy performed for another reason. Many women in whom DCIS was detected early may not be destined to have an invasive carcinoma. How should subclinical DCIS be treated if that is the case? What is the role of excision and surveillance only as an alternative to mastectomy or irradiation?. Methods. All patients with DCIS detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(64 citation statements)
references
References 12 publications
2
61
0
1
Order By: Relevance
“…Most previous studies of recurrence following treatment of DCIS have found a higher incidence of both DCIS and invasive carcinoma following high-grade DCIS, at least in the short term (Lagios et al, 1989;Schwartz et al, 1992;Bellamy et al, 1993;Solin et al, 1993;Sneige et al, 1995;Silverstein et al, 1996;Fisher et al, 1999). In the EORTC study, although the risk of DCIS recurrence was found to be significantly related to the initial histology, the risk of invasive recurrence was not (Bijker et al, 2001a).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most previous studies of recurrence following treatment of DCIS have found a higher incidence of both DCIS and invasive carcinoma following high-grade DCIS, at least in the short term (Lagios et al, 1989;Schwartz et al, 1992;Bellamy et al, 1993;Solin et al, 1993;Sneige et al, 1995;Silverstein et al, 1996;Fisher et al, 1999). In the EORTC study, although the risk of DCIS recurrence was found to be significantly related to the initial histology, the risk of invasive recurrence was not (Bijker et al, 2001a).…”
Section: Discussionmentioning
confidence: 95%
“…Owing to the potential for metastasis, the latter are of considerable significance as the chance of successful eradication of the disease may have been lost. In several studies the incidence of recurrence, at least in the short term, has been found to be higher following high-grade (poorly differentiated) DCIS than following low-grade (well differentiated) lesions (Lagios et al, 1989;Schwartz et al, 1992;Bellamy et al, 1993;Solin et al, 1993;Sneige et al, 1995;Silverstein et al, 1996;Fisher et al, 1999). Moreover, in some studies, the incidence of an invasive recurrence has been found to be higher after high-grade DCIS than after low-grade lesions (Lagios et al, 1989;Bellamy et al, 1993).…”
mentioning
confidence: 99%
“…Although, RT is shown to be effective on local tumor, BCS without postoperative RT has been widely used for the treatment of DCIS. The largest series of 256 patients was reported by Schwartz et al 21 At a median follow-up of 66.5 months (range: 12-247 months), there have been 71 second ipsilateral breast recurrences (27.7%), including 26 invasive (37%) and 45 DCIS only (63%) recurrences. The 10-year actuarial local recurrence rate was 41% with the long-term projection of local recurrence being as high as 50% at 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…As DCIS recurrences occur most often in the same quadrant 4,[27][28][29] and have similar pathological characteristics to the original tumor, 30 it has been suggested that they might be related to residual tumor. Various studies have shown that margin involvement is a risk factor for local recurrence.…”
Section: Discussionmentioning
confidence: 99%